PENGELOLAAN KOTA-KOTA KECIL DI JAWA TENGAH: STUDI KASUS PADA EMPAT KOTA KECIL DI WILAYAH JOGLOSEMAR - Jawoto Sih Setyono; Hadi Sabari Yunus; Sri Rum Giyarsih (TATALOKA, 2017)
Small cities and towns in Indonesia have experienced a significant development during the period of 2000-2010. However, the development of small cities and towns has not been in line with the way the urban areas are governed and managed. There is a tendency that the governments pay a little attention to the governance of smaller urban areas, especially those which do not municipal status or the urban areas which is part of regency administrative boundary. This research analyzes the governance and planning of small towns in Central Java taken four small towns in Joglosemar region (Yogyakarta-Surakarta-Semarang). The research applied some qualitative methods combining document analysis, interview and regulation analysis. It is found that there is a significant gap between the urban development and its planning and governance. Urban development policies seem to be lacking in providing guidelines to drive the development of the small towns so that they can perform their functions within their respective regional urban system as well as solve their internal problems. The governance has mostly relied on the role of local government despite continuing lack of institutional capacity in managing urban development.